Trimethylsilylcellulose synthesis revisited. (April 2017) - Carapeto, A.P.; Ferraria, A.M.; Botelho do Rego, A.M.
Abstract: A simplification of the overall method of producing trimethylsilylcellulose solutions in common organic volatile solvents is reported. Microcrystalline cellulose was derivatized aiming its solubilization in tetrahydrofuran and toluene to obtain ultra-thin films of cellulose by spin-coating. The main simplifications are: 1) elimination of a swelling step before dissolution in the binary solvent N, N -dimethylacetamide/LiCl by using microcrystalline cellulose; 2) derivatization of cellulose –OH groups with –Si(CH3 )3 groups was successful with no additional catalyst, like trimethylsilyl chloride, the degree of substitution (DS) being 2.2 ± 0.1. The DS at the extreme surface of the films was computed from the X-ray Photoelectron Spectroscopy data: using solely C 1s fitted component areas and, alternatively, from both C 1s and Si 2p areas. The DS estimated with a technique specific of the surface is close to the bulky one obtained from gravimetric measurements reported in the literature for materials synthesized with catalyst. The topographic uniformity is shown by Atomic Force Microscopy.